MAPPING THE LANDSCAPE AND RESEARCH AGENDA OF MSME PERFORMANCE THROUGH SHARIA FINANCIAL LITERACY, SHARIA FINTECH,AND DIGITAL READINESS OF ISLAMIC FINANCE: BIBLIOMETRIK ANALYSIS - Sev Rahmiyanti; Agung Praptapa; Puji Lestari; Eliada Herwiyanti (Al-Infaq Jurnal Ekonomi Islam, 2026)
This study aims to map the research landscape and future research agenda on MSME performance through Islamic financial literacy, Islamic fintech, and Sharia digital financial readiness. A bibliometric approach was employed using publication data retrieved from the Dimensions database and analyzed with VOSviewer. The analysis included network visualization, overlay visualization, and density visualization to identify research clusters, thematic trends, and keyword density. The results reveal that financial literacy, Islamic financial literacy, technology, adoption, and fintech adoption are the most dominant themes in the literature. Network analysis indicates strong interconnections among Islamic financial literacy, technology adoption, and fintech-related studies. Overlay visualization shows an increasing research focus on digital transformation, innovation, and fintech adoption, while density visualization highlights financial literacy and technology as the most intensively studied topics. The findings demonstrate that the literature has evolved toward integrating financial literacy, Islamic fintech, and digital readiness in explaining MSME performance. This study contributes by providing a comprehensive overview of the intellectual structure and future research directions in the field of Islamic digital finance and MSME development.